Design and Implementation of Solar Energy in ATG, CCDS and Pantry Maintenance Monitoring Systems - Kamil, Muhammad Insan; Arifin, Fatahul; Dewi, Tresna (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This study aims to design, implement, analyze and evaluate the PV system used in the ATG, CCDS and Maintenance Pantry Monitoring Systems. This study was conducted at PT. Pertamina Patra Niaga, with data collection carried out from June 2024. As for the experimental design carried out to determine the reliability of the equipment made which will be used for ATG motoring, CCDS and Pantry Maintenance, this was carried out to reduce the consumption of fossil energy which has been used through Electricity from PLN. The research results show that the use of the PV system can work optimally, this can be seen from the results of observations, especially at its peak, namely on June 29 2024, namely 2106 watts with a maximum voltage of 84.2V and with the installation of MPPT to ensure there is no overcharging and regulate the input voltage at 29.2V. V to batteries, efficient and effective in replacing previously used conventional energy.